Answer:
(x+2)(3x+1)
Step-by-step explanation:
The total cost for plumber number 1 expressed as a function of x is
c1(x)=45x+90
That is, the charge per hour times the number of hours plus the fixed charge for a visit.
Using the same pattern, write the function for the second plumber. Then set the two functions equal to each other and solve for
<u>Given</u>
- a = m(2) + 2
- value of a when m = -3
<u>Substitute m with -3</u>
a = -3*2 + 2
a = -6 + 2
a = -4
<u>Answer</u>
The value of a when m = -3 is -4
Answer:
B I think or C or D or it could be A